The rise of carry : the dangerous consequences of volatility suppression and the new financial order of decaying growth and recurring crisis - Lee, Tim (Economist); Lee, Jamie (Economist); Coldiron, Kevin (McGrawHill, 2020)
Protect yourself from the next financial meltdown with this game-changing primer on financial markets, the economy-and the meteoric rise of carry. The financial shelves are filled with books that explain how popular carry trading has become in recent years. But none has revealed just how significant a role it plays in the global economy-until now. A groundbreaking book sure to leave its mark in the canon of investing literature, The Rise of Carry explains how carry trading has virtually shaped the global economic picture-one of decaying economic growth, recurring crises, wealth disparity, and, in too many places, social and political upheaval. The authors explain how carry trades work-particularly in the currency and stock markets-and provide a compelling case for how carry trades have come to dominate the entire global business cycle. They provide thorough analyses of critical but often overlooked topics and issues, including: •The active role stock prices play in causing recessions-as opposed to the common belief that recessions cause price crashes •The real driving force behind financial asset prices •The ways that carry, volatility selling, leverage, liquidity, and profitability affect the business cycle •How positive returns to carry over time are related to market volatility-and how central bank policies have supercharged these returns Simply put, carry trading is now the primary determinant of the global business cycle-a pattern of long, steady but unspectacular expansions punctuated by catastrophic crises. The Rise of Carry provides foundational knowledge and expert insights you need to protect yourself from what have come to be common market upheavals-as well as the next major crisis.